Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (Sakti) Dalam Pelaporan Keuangan Pada Biro Keuangan Dan Aset Kementerian Dalam Negeri - Dozan, Willy; Soemartono, Triyuni; Pakpahan, Roy Tumpal (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. This research discusses the implementation of the Financial Application System at the institutional level (SAKTI) in financial reporting, particularly in the context of facing the system transformation implemented through the SAKTI Application. The purpose of this study is to analyze user acceptance of the implementation of the SAKTI Application at the Bureau of Finance and Assets of the Ministry of Home Affairs, using indicators from the Unified Theory of Acceptance and Use of Technology (UTAUT). Materail and methods. This study uses a critical theory approach with a descriptive qualitative research design, conducted through interviews and literature study. The research subjects were selected using purposive sampling, involving 11 informants who are users of the SAKTI Application out of 68 individuals involved. The results of the study indicate that user acceptance of the SAKTI Application varies, classified as neutral, positive, and negative acceptance. This variation is influenced by differences in the ability of human resources to face system transformation, work environment conditions, and workloads. To address negative acceptance, the suggested strategies include updating the utility of the SAKTI Application, improving implementation governance, and strengthening internal support at the institutional level. Cunclotion. This research is expected to contribute to the development of the SAKTI Application and improve the effectiveness of the implementation of financial application systems in the government environment.